The plasma membrane-localized OsNIP1;2 mediates internal aluminum detoxification in rice - Wang, Yuqi; Yang, Shaohua; Li, Chune; Hu, Taijiao; Hou, Siyu; Bai, Qing; Ji, Xiyue; Xu, Feng; Guo, Chongdai; Huang, Min; Cai, Yanfei; Liu, Jiping (Frontiers in Plant Science, 2022)
Aluminum (Al) toxicity significantly restricts crop production in acidic soils. Although rice is highly resistant to Al stress, the underlying resistant mechanisms are not fully understood. Here, we characterized the function of OsNIP1;2, a plasma membrane-localized nodulin 26-like intrinsic protein (NIP) in rice. Aluminum stress specifically and quickly induced OsNIP1;2 expression in the root. Functional mutations of OsNIP1;2 in two independent rice lines led to significantly enhanced sensitivity to Al but not other metals. Moreover, the Osnip1;2 mutants had considerably more Al accumulated in the root cell wall but less in the cytosol than the wild-type rice. In addition, compared with the wild-type rice plants, the Osnip1;2 mutants contained more Al in the root but less in the shoot. When expressed in yeast, OsNIP1;2 led to enhanced Al accumulation in the cells and enhanced sensitivity to Al stress, suggesting that OsNIP1;2 facilitated Al uptake in yeast. These results suggest that OsNIP1;2 confers internal Al detoxification via taking out the root cell wall’s Al, sequestering it to the root cell’s vacuole, and re-distributing it to the above-ground tissues.